Precipitation–deposition synthesis, characterization, and visible light-driven photocatalytic properties of heterostructure AgI/Bi2WO6 nanocomposites - Anukorn Phuruangrat (2019)
© 2018, Australian Ceramic Society. AgI nanoparticle-modified Bi2WO6 nanoplates were prepared by a precipitation–deposition method. X-ray diffraction and transmission electron microscopy certified the formation of hexagonal AgI nanoparticles with the size of 5–8 nm as minor phase well supported on orthorhombic Bi2WO6 nanoplates as major phase. The photocatalytic properties of heterostructure AgI/Bi2WO6 nanocomposites were investigated through photodegradation of rhodamine B (RhB) induced by xenon visible light. The 10 wt% AgI/Bi2WO6 nanocomposites exhibited the highest photocatalytic activity because of the recombination rate reduction of photoexcited electrons and photogenerated holes during photocatalysis. A possible photodegradation mechanism of RhB by AgI/Bi2WO6 nanocomposites was proposed and discussed in this research.